2018
DOI: 10.1029/2018wr023091
|View full text |Cite
|
Sign up to set email alerts
|

Water Source Signatures in the Spatial and Seasonal Isotope Variation of Chinese Tap Waters

Abstract: Different water sources exploited for public use have different exposure to risks associated with climatic and environmental change. Isotope ratios of tap water have previously been studied as a potential tool to link public supply waters with water source characteristics at local to continental scales, providing information on the footprint of and potential risks associated with the water sources used. Work that combines intensive spatial and temporal sampling with independent water management data has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…In the existing tap water isotope studies [23,42] on large scales, it has been proved that isotopes in tap water mainly supplied by surface water show good correlation with precipitation isotopes [42]. Our conclusion supplements the analysis of tap water source based on the isotopes method at different spatial scales.…”
Section: Determination Of Tap Water Source Based On Isotope Datasupporting
confidence: 68%
See 2 more Smart Citations
“…In the existing tap water isotope studies [23,42] on large scales, it has been proved that isotopes in tap water mainly supplied by surface water show good correlation with precipitation isotopes [42]. Our conclusion supplements the analysis of tap water source based on the isotopes method at different spatial scales.…”
Section: Determination Of Tap Water Source Based On Isotope Datasupporting
confidence: 68%
“…Zhao et al [38] presented the spatiotemporal variations of δ 2 H and δ 18 O in tap water in China and analyzed the relationship between isotopes in tap water and topographic and meteorological factors. Wang et al [42] analyzed the connection between monthly stable isotopes in tap water and precipitation based on a new nationwide network of tap water isotope data across China, and found that the diagnostic patterns of isotopes in tap water were associated with water resource use. As a whole, studies on isotopes in tap water are of great significance for enriching the understanding of tap water isotopes characteristics, environmental effect elements and water sources [23,24,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, studies on isotopes in tap water [33,34] throughout the world are relatively few. Their study areas have mainly involved the United States of America (e.g., the San Francisco Bay Area [31], the Salt Lake Valley of northern Utah [30], western and the whole United States [35][36][37]), South Africa [30], and China [34,38]. The main research contents include basic features (e.g., spatial and temporal variations, local tap water line) of tap water isotopes, tap water source, the applicability of tap water to relevant fields, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…In urban settings, stable isotopes and other geochemical tracers have been used successfully to understand effects of storm water control measures on urban streams (Jefferson et al, 2015), detect infiltration rates in urban sewers (De Bénédittis et al, 2005;Kracht et al, 2007), partition waste water and groundwater in urban sewers (De Bondt et al, 2018), and determine the age of drinking water in PWSS (Waples et al, 2015). Recent studies have also shown that stable isotopes of tap water in urban areas can be used to characterize active water management practices, identify linkages between socioeconomic factors and water management practices, and quantify the effects of climate variability on water resources Tipple et al, 2017;Zhao et al, 2017, Wang et al, 2018.…”
Section: Introductionmentioning
confidence: 99%